ANALISIS KEMAMPUAN PEMECAHAN MASALAH MODEL POLYA MATERI GETARAN, GELOMBANG, DAN BUNYI SISWA SMP - Astuti, Nurul Heni; Rusilowati, Ani; Subali, Bambang; Marwoto, Putut (UPEJ Unnes Physics Education Journal, 2020)
This study aims to determine the problem solving ability of  the 9th grade students of  Banyubiru 1 and 2 Junior High School in 2019/2020 in the material of wave, and sound. This is a survey research with descriptive qualitative analysis. The instrument used was an integrated test with Polya's model problem solving steps and interview guidelines. Test questions tested consists of 2 problem descriptions. The result shows that the ability of the students  problem solving ability was still at the low level which is at 68.97%. Whereas,  90.32% of students' score are still below the minimum completeness criteria (KKM) in science subject. Students are able to achieve 2 indicators of Polya model problem solving namely understanding the problem and making plans.  However, students have not yet been able to achieve the other 2 indicators, namely  implementing the plan and checking again. The students found the difficulties in interpreting the Problem-type questions. They got difficult in understanding the intentions of the problem so that there is an error in compiling a strategy that results in students experiencing confusion in writing each answer. So training is needed in working on problem solving problems.